Dislocation emission caused by different types of nanoscale deformation defects in CdTe - Babentsov, V.N.; Boyko, V.A.; Gasan-zade, S.G.; Shepelski, G.A.; Stariy, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Dislocation-related defects induced by dislocation motion in p-CdTe were studied. Generation of “fresh” dislocations from the indented point of the CdTe (100), (110), and (111) surfaces at room temperatures was visualized by chemical etching and low temperature photoluminescence in a mapping regime. The crystallographic orientation of the dislocation rosettes of macroscopic plastic deformation lines was analyzed on the (100), (110), and (111) surfaces.